Investigating the effects of using concordance data on vocabulary acquisition in an Egyptian English for academic purposes setting - Steiner, Jenna (AUC Knowledge Fountain, 2011)
The purpose of the present study was to investigate the effects of using concordance data in the classroom on vocabulary acquisition in the English Language Institute (ELI) at the American University in Cairo (AUC). Specifically, the effects on overall lexical knowledge and ability to distinguish between synonyms were explored in addition to students' attitudes towards the use of concordance data. This study employed an exploratory and quantitative approach and used a convenience sample of six intact Egyptian EFL university classes. Three classes with a total of 26 participants were randomly assigned to the experimental group and the remaining three classes with a total of 24 participants were assigned to the control group. The researcher administered a pretest, a vocabulary lesson, and a posttest to each group. The experimental group also completed a questionnaire on their feelings towards the use of concordance lines. The results of the quantitative data indicated that both the experimental and the control group made statistically significant gains from pretest to posttest. However, neither group made higher gains than the other, thus suggesting that there was no difference between the two groups in overall lexical knowledge or ability to distinguish between synonyms. Meanwhile, the qualitative data revealed a positive attitude of behalf of the participants towards the use of concordance lines in their classrooms.